PROGNOSTIC FACTORS OF RELAPSE IN THE SURGICAL TREATMENT OF DESMOID FIBROIDS OF THE TRUNK AND EXTREMITIES - A. V. Yadrina; V. Yu. Karpenko; O. V. Novikova; N. M. Bychkova; V. A. Derzhavin; A. V. Bucharov (Исследования и практика в медицине, 2019)
Purpose of the study. Evaluation of the results of surgical treatment of desmoid fibroids (DF) using reconstructive plastic surgery and determination of possible prognostic factors of relapses.Patients and methods. The results of surgical treatment of 40 patients with desmoid fibroids of extra abdominal localization were analyzed. In 45% of patients, the tumor was located in soft tissues of the shoulder girdle and upper limb, in 35% — on the trunk, in 20% — in soft tissues of the lower limb and in 7% of patients on the neck. The tumor size varied from 2 to 20 cm, the median was 8 ± 4.38 cm. Surgical treatment for newly diagnosed DF was performed in 22 (55%) patients, and for recurrent tumors — in 18 (45%) patients.Results. According to the planned histological study, negative resection boundaries were established in 24/40 patients (63%). In the remaining 16 cases (37%) positive resection margins were obtained: R1 in 14 patients and R2 in 2 patients. Adjuvant treatment is recommended for 14 patients with resection R1/R2. The duration of follow — up after treatment ranged from 6 to 107 months, median‑16.5 months. During follow-up, relapses were diagnosed in 14 patients (35%). No deaths have been reported.Conclusion. Surgical treatment of DF of extraabdominal localization is accompanied by a sufficiently high frequency of relapses. According to the results of the study, an unfavorable factor in the development of relapses is the location of the tumor in soft tissues of the shoulder girdle and upper limb.